Mortandad masiva de Mesodesma mactroides (Bivalvia: Mactracea) en el Partido de la costa, Buenos Aires, Argentina, en septiembre 2004 - Thompson, Gustavo A.; Sanches de Bock, Mariana F. ((DESCONTINUADA) Atlântica, 2011)
Massive mortality of Mesodesma mactroides (Bivalvia: Mactracea) in Partido de la Costa, Buenos Aires, Argentina in September 2004 Yellow clam Mesodesma mactroides has been decreased by several events of massive mortality along its distribution in Brazil, Uruguay and Argentina. This study evaluates and compares concentrations of As, Cd, Cr, Cu, Ni, Pb and Zn, in the tissues of clams collected during an event of massive mortality, in September 2004 and one year after. Quantification of heavy metals was realized by acid digestion and later determination by spectrometry. Values of Cd, Cu and Pb (11 ± 2, 42 ± 4 and 7 ± 1 mg/kg dry weight, respectively) in clam tissues during mortality event were higher than the ones registered one year later. Value of Cd in clams during the mortality ( 1.5 mg/kg wet weight) was superior to the maximum limit of tolerance for the human consumption. Absence of Cd in sediments and seawater, suggests that the clams suffered a process of punctual and acute pollution. Mortality could have been the result of a set of factors that affected the subtidal population of yellow clam: climatic adverse conditions can "extracted" from the bottom and dragged to the beach the specimens, whose physiology was altered by an isolated event of pollution with heavy metals.